2008
DOI: 10.3945/jn.108.099663
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Biodistribution Is Altered in 15,15´-Carotenoid Monooxygenase Knockout Mice3

Abstract: 15,15'-carotenoid monooxygenase (CMO I) is generally recognized as the central carotenoid cleavage enzyme responsible for converting provitamin A carotenoids to vitamin A, while having little affinity for nonprovitamin A carotenoids, such as lycopene. To investigate the role of CMO I in carotenoid metabolism, approximately 90-d-old C57BL/6 x 129/SvJ [CMO I wild-type (WT)] and B6;129S6-Bcmo1tm1Dnp [CMO I knockout (KO)] mice were fed a high-fat, moderate vitamin A, cholesterol-containing diet supplemented with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
4
30
1
Order By: Relevance
“…Regardless, the b-cryptoxanthin gene score was significantly inversely associated with plasma retinol in the testing subset, and the b-carotene gene score, when weighted for retinol, was significantly associated with plasma retinol in all women with genotyped data for the relevant SNPs. Liver retinol stores may be more affected by BCMO1 variation, as suggested by the reduced liver vitamin A concentrations in b-carotene-fed BCMO1 knockout mice (31,32). Overall, our results support the hypothesis that BCMO1 variants affect provitamin A carotenoid conversion, presumably because of altered BCMO1 function (7,9).…”
Section: Discussionsupporting
confidence: 75%
“…Regardless, the b-cryptoxanthin gene score was significantly inversely associated with plasma retinol in the testing subset, and the b-carotene gene score, when weighted for retinol, was significantly associated with plasma retinol in all women with genotyped data for the relevant SNPs. Liver retinol stores may be more affected by BCMO1 variation, as suggested by the reduced liver vitamin A concentrations in b-carotene-fed BCMO1 knockout mice (31,32). Overall, our results support the hypothesis that BCMO1 variants affect provitamin A carotenoid conversion, presumably because of altered BCMO1 function (7,9).…”
Section: Discussionsupporting
confidence: 75%
“…This is consistent with the relevant findings from other groups (Amengual et al, 2013; dela Sena et al, 2013; Dela Sena et al, 2016; Lindqvist and Andersson, 2002; Lindshield et al, 2008; Mein et al, 2011; Wang, 2012). Our feeding data also revealed that in bco1 −/− /bco2 −/− mice, the retinal accumulation of xanthophylls lutein and zeaxanthin is around six times higher than retinal accumulation of β-carotene, while the hepatic β-carotene is around twenty times as much as the hepatic xanthophyll.…”
Section: Discussionsupporting
confidence: 93%
“…For the crystalline zeaxanthin bioavailability study, zeaxanthin was mixed with the vitamin-A-deficient AIN-93G diet (1 g/kg) prepared by Test Diet (St. Louis, MO, USA). Zeaxanthin encapsulated DSM ActiLease ® beadlets were mixed with a previously reported base diet (Lindshield et al, 2008) at a dosage of 1 g/kg of the base diet.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, we conclude that CMO-I and CMO-II appear to have pleiotropic roles in lipid metabolic homeostasis. We [24,29] and others [68,13] have established that tomato carotenoids are likely substrates of these enzymes. Additionally, the expression of CMO-I and CMO-II alter serum, adipose, and hepatic lipid products.…”
Section: Discussionmentioning
confidence: 99%
“…Total liver lipids were extracted using a modification of the Folch method [28,29]. Briefly, the liver sample (~0.3 g), n = 10 per group, was homogenized in chloroform: methanol (1:1) (Fisher Scientific, Pittsburg, PA.) and filtered by gravity.…”
Section: Methodsmentioning
confidence: 99%